SISTEM INFORMASI PENJUALAN BARANG PADA PERUSAHAAN PT. PYRIDAM FARMA TBK BANDA ACEH - Ulvia, Khaira (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The aim of this research is; 1) To find out the sales information system at PT. Pyridam Farma Tbk Banda Aceh, and 2) To design a sales information system at PT. Pyridam Farma Tbk Banda Aceh web-based researchers compiled using a flow chart where the data describes the flow of data from a process that is often referred to as an information system. While in the process of developing the prototype using the agile development method. Based on the results of observations and the author can draw a conclusion which includes the following; 1) The use of sales information systems at PT. Pyridam Farma is expected to be able to help make sales information data accurate and effective, 2) With the information system, it is easy for PT. Pyridam Farma for speeding up information in general and reducing errors, and 3) Sales Information System at PT. Pyridam Farma which the author designed uses various web-based programming languages ​​consisting of; HTML, CSS, Jquery, Java Script, JSON PHP, and for database processing used is Structure Query Language (SQL). The supporting software used is XAMPP version 5.6 (Support MySQLi), NotePad ++, and Google Chrome Browser.